2022
DOI: 10.1093/geroni/igac032
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Cardiometabolic Risk Factors and Frailty in Older Adults: A Systematic Review

Abstract: Background and Objectives Enhanced management and prevention of frailty depend on our understanding of the association between potentially modifiable risk factors and frailty. However, the associations between potentially modifiable cardiometabolic risk factors and frailty are not clear. The purpose of this review was to appraise and synthesize the current evidence examining the associations between the cardiometabolic risk factors and frailty. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 67 publications
1
9
0
Order By: Relevance
“…Among chronic conditions, overweight and obesity show an increasing prevalence across the world, affecting people of all ages [59], and particularly in case of abdominal adiposity, they are associated with an increased CVR [60]. In older adults, abdominal obesity, along with other cardiometabolic risk factors, is associated with a greater likelihood of frailty [61], a state of compromised homeostasis which predisposes to adverse health outcomes [62]; moreover, especially in the elderly, obesity is frequently associated with sarcopenia, generating a condition defined sarcopenic obesity [63,64] A recent meta-analysis, including both adults and older adults, revealed a high prevalence of physical inactivity and sedentary behavior among people with obesity, and a positive association between these factors; this evidence indicates the need of a particular attention and support from health professionals [65].…”
Section: Discussionmentioning
confidence: 99%
“…Among chronic conditions, overweight and obesity show an increasing prevalence across the world, affecting people of all ages [59], and particularly in case of abdominal adiposity, they are associated with an increased CVR [60]. In older adults, abdominal obesity, along with other cardiometabolic risk factors, is associated with a greater likelihood of frailty [61], a state of compromised homeostasis which predisposes to adverse health outcomes [62]; moreover, especially in the elderly, obesity is frequently associated with sarcopenia, generating a condition defined sarcopenic obesity [63,64] A recent meta-analysis, including both adults and older adults, revealed a high prevalence of physical inactivity and sedentary behavior among people with obesity, and a positive association between these factors; this evidence indicates the need of a particular attention and support from health professionals [65].…”
Section: Discussionmentioning
confidence: 99%
“…When comparing the three categories of FLI values in this cohort, alanine aminotransferase (ALT) increased with increasing FLI (median 16 U/L [IQR [13][14][15][16][17][18][19][20] vs. 18 U/L [IQR [14][15][16][17][18][19][20][21][22] vs. 21 U/L [IQR 14-23] respectively). The proportion of those with MASLD and concomitantly abnormal ALT levels at Australian sex-specific cut-offs 42 (females ≥19 U/L, males ≥30 U/L) was only 37.8%; when using less restrictive cut-offs for normal 43 (females ≥25 U/L, males ≥33 U/L), the proportion dropped to 22.0% (Table 3).…”
Section: Abnormal Transaminases and Masldmentioning
confidence: 99%
“…Although the seminal Rotterdam study 14 showed a decreasing prevalence of NAFLD with advancing age, data from NHANES III showed a largely stable prevalence of NAFLD between those aged 60-74 and >74 years. 15 In addition, while multiple markers of dysmetabolism have been shown to be associated with NAFLD in both middle-aged and older adults 14,16 and cardiometabolic risk factors have been previously linked to socioeconomic status 17 and frailty, 18 direct associations between NAFLD and frailty, impaired physical mobility, or social disadvantage are less well studied but mechanistically plausible. Previous work has shown that NAFLD is associated with cardiac, 19 renal, 20 and pulmonary diseases, 21 as well as sarcopenia, all of which may predispose to the development of these important clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a global population‐level study summarizing 240 studies from 62 countries concluded that the frailty prevalence ranged between 12% (FP approach) and 24% (FI approach), while that of prefrailty ranged between 46% (FP approach) and 49% (FI approach) 9 . Risk factors for frailty include advanced age, female sex, anthropometric features (abdominal obesity), ethnic minorities, multimorbidity and individual illnesses (hyperglycemia, osteoporosis, and vasculopathy), certain geospatial locations, rural versus urban areas, lifestyle factors, and so forth, 10–13 while hypertension and dyslipidemia exhibit an inconsistent relationship 14 …”
Section: Frailty: An Introductory Overviewmentioning
confidence: 99%
“…9 Risk factors for frailty include advanced age, female sex, anthropometric features (abdominal obesity), ethnic minorities, multimorbidity and individual illnesses (hyperglycemia, osteoporosis, and vasculopathy), certain geospatial locations, rural versus urban areas, lifestyle factors, and so forth, [10][11][12][13] while hypertension and dyslipidemia exhibit an inconsistent relationship. 14 However, the adverse effects of frailty cannot be overlooked.…”
mentioning
confidence: 99%